Recent advances of IDH1 mutant inhibitor in cancer therapy - Tian, Wangqi; Zhang, Weitong; Wang, Yifan; Jin, Ruyi; Wang, Yuwei; Guo, Hui; Tang, Yuping; Yao, Xiaojun (Frontiers in Pharmacology, 2022)
Isocitrate dehydrogenase (IDH) is the key metabolic enzyme that catalyzes the conversion of isocitrate to α-ketoglutarate (α-KG). Two main types of IDH1 and IDH2 are present in humans. In recent years, mutations in IDH have been observed in several tumors, including glioma, acute myeloid leukemia, and chondrosarcoma. Among them, the mutation frequency of IDH1 is higher than IDH2. IDH1 mutations involve an increase in the activity of the new form that catalyzes the conversion of α-KG to 2-hydroxyglutarate (2-HG). IDH1 mutation-mediated accumulation of 2-HG leads to epigenetic dysregulation, altered gene expression, and impaired cell differentiation. A rapidly emerging therapeutic approach is through the development of small molecule inhibitors targeting mIDH1, as evidenced by the recently approved first selective mutant IDH1 inhibitor AG-120 (ivosidenib) for the treatment of IDH1-mutated AML. This review will focus on mIDH1 as a therapeutic target and provide an update on mIDH1 inhibitors in clinical trials and other mIDH1 inhibitors in development.